International cooperation in the post-pandemic era - Garcia, Denise (2022)
ADVOCATUS had the chance to interview Denise García, a Brazilian expert on international relations, about the development of international cooperation and the role that the Law plays in it. García is a PhD on International Relations by the Institut des Hautes Études Internationales et du Développement of Geneva, and currently holds tenure at Northeastern University in Boston, teaching in the Department of Political Science and the program of International Affairs. In the following lines, Dr. García develops her vision on the current international relations, the importance of international relations in the efforts to defeat the COVID-19 pandemic, the role that the private sector plays in the geopolitical scenario, the main challenges that the international community faces and how International Law is the underlying thread in the cooperation among the different actors, public and private.